Isogeometric nonlinear bending analysis of porous FG composite microplates with a central cutout modeled by the couple stress continuum quasi-3D plate theory - Rao, Rui; Sahmani, Saeid; Safaei, Babak (Springernature, 2021)
In the present investigation, by putting the isogeometric finite element methodology to use, the nonlinear flexural response of composite rectangular microplates having functionally graded (FG) porosity is predicted incorporating couple stress type of small scale effect. To accomplish this analysis, a non-uniform kind of rational B-spline functions are employed for an accurate geometrical description of cutouts with various shapes located at the center of microplates. The modified couple stress continuum elasticity is implemented within the framework of a new quasi-three-dimensional (quasi-3D) plate theory incorporating normal deflections with only four variables. By refining the power-law function, the porosity dependency in conjunction with the material gradient are taken into consideration in a simultaneous scheme. The couple stress-based nonlinear flexural curves are achieved numerically based upon a parametrical study. It is demonstrated that for a larger plate deflection, the role of couple stress type of small scale effect on the nonlinear bending curves of porous FG composite microplates is highlighted. It is seen that the gap between nonlinear flexural responses associated with different through-thickness porosity distribution schemes is somehow higher by taking the couple stress effect into account. Also, it is observed that the existence of a cutout at the center of composite microplates makes a change in the slope of their nonlinear flexural curve.
Keywords: Couple stress continuum mechanics; Quasi-3D plate model; Isogeometric numerical technique; Small scale effect; Porous composite material